2017
DOI: 10.1038/s41564-017-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa defends against phages through type IV pilus glycosylation

Abstract: Since phages present a major challenge to survival in most environments, bacteria express a battery of anti-phage defences including CRISPR-Cas, restriction-modification and abortive infection systems . Such strategies are effective, but the phage genome-which encodes potentially inhibitory gene products-is still allowed to enter the cell. The safest way to preclude phage infection is to block initial phage adsorption to the cell. Here, we describe a cell-surface modification that blocks infection by certain p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 50 publications
0
95
0
6
Order By: Relevance
“…While fewer in number to date, other phages have been discovered to use pili as their primary receptor (Harvey et al, 2018, McCutcheon et al, 2018. Kropinski et al (2012) have argued that this general mechanism of binding to extended filaments increases the probability of encountering the target bacterium, since bacteria with their flagella extended have a capture radius 5-to 10-fold greater than the bacterial cell itself (Kropinski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While fewer in number to date, other phages have been discovered to use pili as their primary receptor (Harvey et al, 2018, McCutcheon et al, 2018. Kropinski et al (2012) have argued that this general mechanism of binding to extended filaments increases the probability of encountering the target bacterium, since bacteria with their flagella extended have a capture radius 5-to 10-fold greater than the bacterial cell itself (Kropinski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many bacteriophages use extracellular appendages such as pili as receptors during infection (12)(13)(14). It is thought that phage particles bind to pili, which retract and pull the phage to the cell body, where infection occurs.…”
mentioning
confidence: 99%
“…First is the hypothesis that Phaeobacter phage MD18 recognizes type IV pili as its receptor. These surface structures have been found to be common targets of phages (31)(32)(33) and several of their components exhibit significant sequence and structural similarities with bacterial Type II secretion systems (34)(35)(36). The relationship between Type IV pili and Type II secretion systems is extensive and it has even been shown that overexpression of certain Type II components results in the formation of pili (30,37).…”
Section: Discussionmentioning
confidence: 99%